Several Physiological Changes of Cocoa (Theobroma cacao L.) in Response to Vascular Streak Dieback Diseases - Teguh Iman Santoso; Fakhrusy Zakariyya (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
The physiological response of cocoa plants under VSD infections is still limited because there is no method in artificial inoculation since Oncobasidium theobromae was reported as parasitic obligates. The investigation of correlation between cocoa responses and VSD attack becomes important information to figure out the effect of decreased productivity as the consequences of the physiological damages. The objective of this research was to describe the pathogen infection and the symptom of VSD through fungal staining method and to asses the changes of some physiological aspects (chlorophyll and gass exchange character) under VSD pathogen infection. This study was conducted in Kaliwining experimental station, ICCRI, Jember, East Java, Indonesia. The result of the study indicated that late infection stage caused chlorophyll degradation, decreasing transpiration rate, and increasing temperature in both tolerant clone (Scavina 6) and susceptible clone (TSH 858). The rate of photosynthesis, stomatal conductance, and concentration of CO2 in susceptible clone (TSH 858) showed a drastic decrease when infected by VSD pathogen than that of in healthy plants. In resistant clone (Scavina 6), photosynthesis rate, stomatal conductance, and concentration of CO2 showed no significant decrease when infected by VSD pathogen compared to that non-infected condition.